Internalization Mediation towards the Relationship between Entrepreneurial Action and Individual Performance for the Next Generation of Family Companies in Surabaya - Carolina Novi Mustikarini (Universitas Hayam Wuruk Perbanas, 2017)
This studyÂ examined the effect of entrepreneurial action for the performance of the next generation using the sample of students who joined the Family Business Community. In this study, there is a high contribution given by the role of entrepreneurship education in preparing the next generation in the family business. In addition, entrepreneurship education is considered possible through the process of internalization of the leaning process that is going on. For example, it is noted that entrepreneurial action can have a significant effect on the performance of the organization. In the context of the family business and entrepreneurial education at the University of Ciputra, both variables (entrepreneurial action and individual performance) are necessary to be tested and therefore, the researcher finds it possible to cary out a research that is supposed to have a contribution to the family business. This study uses a hierarchical regression analysis, to test the stages of the mediation process. The results showed that most of relationships mediate internalization Entrepreneurial Action and Individual Performance.